Degradation of diesel oil by microorganisms isolated from lagoons of the “Totora” wastewater treatment plant, Ayacucho - Chuchón-Martínez, Saúl Alonso; Delgadillo-Coronado, Pedro Mauricio; Gastelu-Quispe, Rilder Nemesio; Cruz, Ruth Elsa Huaman-De La; Rivera-Villar, Jime Jack; Marín-Sánchez, Obert (Edelweiss Applied Science and Technology, 2025)
The degradation of oil by microbial consortia isolated from maturation ponds of the Wastewater Treatment Plant "Totora," Ayacucho, was evaluated. Samples were collected from three ponds and transported to the Environmental Microbiology Laboratory - UNSCH. The microorganisms were isolated by inoculating 10 mL of sample in Bushnell-Haas medium with 4% v/v oil, incubated at room temperature with shaking for 21 days. They were then cultured on nutrient agar and Sabouraud agar, by surface exhaustion, incubated at 37°C and 25°C, respectively. The strains were grouped into three consortia by origin (LM1, LM2, and LM3; each composed of four bacterial strains and six mold strains), with which soils containing one, four, eight, and 16% oil were bioremediated in vitro, in plastic containers with one kg of agricultural soil, with three repetitions, each treatment inoculated with 10 mL (1.5 x 10^8 CFU/mL) of each strain of the consortium, with a blank per treatment without inoculant. They were evaluated every 14 days for 70 days, measuring residual oil by agitation-centrifugation and gravimetry. The LM2 consortium achieved better results, with oil removals of 100%, 100%, 92%, and 42% in soils with one, four, eight, and 16% oil, respectively. The strains of the LM2 consortium were: LM2A-1, LM2A-2, LM2B-1, and LM2B-2 (Gram-negative bacteria), LM2A-1 and LM2B-1 (Penicillium sp.), LM2A-2 (Pithomyces sp.), LM2A-3 (Wallemia sp.), and LM2A-4 and LM2B-6 (Geotrichum sp.). The ANOVA and Duncan tests indicate that there are significant differences (p ≤ 0.05).